Unveiling an unusual presentation in an unaccustomed syndrome: Intussusception and Peutz-Jeghers - A case report (Indian Journal of Case Reports, 2025)
Peutz-Jeghers syndrome (PJS) is an uncommon hereditary gastrointestinal (GI) polyposis syndrome that is associated with pathognomonic mucocutaneous hyperpigmentation. Here, we present a case of ileoileal intussusception causing acute small bowel obstruction in a young female with PJS. In our patient, we considered PJS due to the findings of intestinal polyposis with mucocutaneous hyperpigmentation in an otherwise young female with a positive family history of similar hyperpigmentation who presented with clinical features suggestive of acute small bowel obstruction and on imaging was confirmed to be secondary to intussusception. She underwent an exploratory laparotomy and bowel resection, followed by endoscopic evaluation of the entire GI tract.